Hubungan Penggunaan Media Sosial Dengan Masalah Kesehatan Mental Anak Usia Sekolah : Studi Cross Sectional Di Sekolah Dasar - Siti Nailatul Maufiroh; Miftakhul Ulfa; Dwi Soelistyoningsih (STIKES Widyagama Husada, 2026)
Abstract Background: Social media is often accessed by young children, including TikTok, Facebook, and YouTube. If it is not controlled, it can cause mental health problems in children, leading to depression, anxiety, difficulty concentrating, and disrupting their academic performance. Objective: To examine the correlation between social media use and mental health in school-age children at SDN Mulyorejo 03. Methods this quantitative research used a cross-sectional approach. The sample consisted of 40 children from fourth, fifth, and sixth grade, selected using purposive sampling. The instruments in this study were questionnaires, namely the Strengths and Difficulties Questionnaire (SDQ) for mental health problems and the Social Media Measurement Intensity Scale (SIMPS). Correlation betwee variables tested using the chi-square test. The results of the study obtained a significant value of p=0.035, indicating a correlation between social media use and mental health problems in children. The level of social media use among children was mostly in the high category, with 18 children (45%). The status of mental health problems was mostly in the highest category, with 21 children (52.5%). Conclusion there is a significant correlation between social media use and mental health problems in school-aged children at SDN Mulyorejo 03. Recommendation this study can add to our knowledge about the negative and positive impacts of social media use among school-aged children.